SMEs and investment in grassroots sport clubs : a United Kingdom perspective - Talbot, Justin (2020)
Researchers have shown that grassroot sports club (GSC) provide many benefits to individuals and the wider community. However, GSCs face increasing pressure to remain financially sustainable, or face extinction. Larger sport organisations have been able to enter into financial agreements with corporations to fund their activities. This thesis considers whether other actors within the community such as Small and Medium sized Enterprises (SME) can play a role to assist in the financial stability and longevity of GSCs, through the provision of financial and/or non-financial sponsorship. The aim of this thesis is to examine whether the benefits large sport properties gain through sponsorship from corporations can also be gained by local GSCs who might look to SMEs sponsorship. This thesis undertakes a multi-case case study with five SME businesses who had existing sponsorship relationships with community organisations to explore and understand the decision making process of SME owners and their views on sponsoring a local GSC. The results highlight that the benefits GSCs provide is not well known by the public. This impacts business owner preferences and risk management in sponsorship decisions. The case studies also provide insight into how SME business strategy and GSC location impacts sponsorship decisions. Ultimately, building long term financial sustainability for GSCs requires knowledge transfer, which can build social capital, enhance relationships and build opportunities for sponsorship. To achieve a successful sponsorship relationship both the SME and the GSC require high degree of knowledge about the other. Future research should focus on how this knowledge transfer can occur.